PENGATURAN LARANGAN RANGKAP JABATAN MENTRI DALAM PERATURAN PERUNDANG-UNDANGAN DI INONESIA - I Komang Trisna Adi Putra (Jurnal Komunikasi Hukum, 2022)
Article 23 of the Law on State Ministries, ministers are prohibited from holding concurrent positions. However, at the Ministry of Defense, which is held by Prabowo Subianto, there was a dual position carried out by Prabowo Subianto where he served as Minister of Defense and general chairman of a political party. Judging from Article 23 of the Law on the Ministry of State, there is ambiguity in letter C, because Prabowo Subianto, apart from being the Minister of Defense, is also the general chairman of a political party. Article 35 paragraph (1) letter c of Law No. 2 of 2011 concerning Political Parties also regulates the existence of financial sources for political parties, namely in the form of financial assistance from the State Revenue and Expenditure Budget (APBN)/Regional Revenue and Expenditure Budget (APBD). Assistance sourced in this case (APBN/APBD) is assistance from the central government and local governments which of course already have arrangements that are in accordance with the needs of the party. Of course, each party does not get the same assistance because the provision of assistance from the central and regional governments sourced from the APBN/APBD is based on or based on the votes obtained by each party in the current Minister of Defense election where he is still the general chairman of a political party when viewed One of the sources of income for political parties in Indonesia is the APBN or APBD. Therefore, concurrent positions carried out by a minister who is also the general chairman of a political party have violated Article 23 letter C of the State Ministerial Law which can interfere with the performance of a minister in carrying out his duties so that the resulting performance cannot be optimal because it is divided by his activities as a general chairman of a political party.